2008
DOI: 10.1007/s12031-008-9163-6
|View full text |Cite
|
Sign up to set email alerts
|

GABA-B1 Receptors are Coupled to the ERK1/2 MAP Kinase Pathway in the Absence of GABA-B2 Subunits

Abstract: In the current model of gamma-aminobutyric acid (GABA) B receptor function, there is a requirement for GABA-B(1/2) heterodimerisation for targetting to the cell surface. However, different lines of evidence suggest that the GABA-B(1) subunit can form a functional receptor in the absence of GABA-B(2). We observed coupling of endogenous GABA-B(1) receptors in the DI-TNC1 glial cell line to the ERK pathway in response to baclofen even though these cells do not express GABA-B(2). GABA-B(1A) receptors were also abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Additionally, the results of the present study show that activation of the ERK1/2-signaling pathway in PPT cells promotes both SWS and REM sleep by suppressing W. Thus, it appears that like in other cell types, in the PPT cells, PKA, CaMKII, and ERK1/2-signaling systems interact to regulate sleep-wake stages. On the basis of present findings and our previous studies as well as the studies of others (Datta et al 2001Datta and Siwek 2002;Vanhoose et al 2002;Paul et al 2003;Wetzker and Bohmer 2003;Ulloor et al 2004;Bandyopadhya et al 2006;Datta 2007;Tu et al 2007;Wang et al 2007Wang et al , 2007Richer et al 2009;Venkitaramani et al 2009;Datta and Desarnaud 2010;Stack et al 2010), we propose a working model for the signal transduction interactions in the PPT that lead to the regulation of sleepwake stages (Fig. 7).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Additionally, the results of the present study show that activation of the ERK1/2-signaling pathway in PPT cells promotes both SWS and REM sleep by suppressing W. Thus, it appears that like in other cell types, in the PPT cells, PKA, CaMKII, and ERK1/2-signaling systems interact to regulate sleep-wake stages. On the basis of present findings and our previous studies as well as the studies of others (Datta et al 2001Datta and Siwek 2002;Vanhoose et al 2002;Paul et al 2003;Wetzker and Bohmer 2003;Ulloor et al 2004;Bandyopadhya et al 2006;Datta 2007;Tu et al 2007;Wang et al 2007Wang et al , 2007Richer et al 2009;Venkitaramani et al 2009;Datta and Desarnaud 2010;Stack et al 2010), we propose a working model for the signal transduction interactions in the PPT that lead to the regulation of sleepwake stages (Fig. 7).…”
Section: Discussionsupporting
confidence: 66%
“…2002; Wetzker and Bohmer 2003; Tu et al. 2007; Richer et al. 2009) and enhances down‐regulation of CaMKII and PKA‐signaling pathways (Datta 2007; Stack et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that intracellular GB1 alone induces ERK1/2 phosphorylation [26]. Here we compared the effect induced either by GB1 or GB1asa.…”
Section: Resultsmentioning
confidence: 94%
“…However, the temporal and spatial expression profiles of GB1 and GB2 do not always coincide [1], [3], [13], [18], suggesting that GB1 is functional in the absence of GB2. Furthermore, several lines of evidence suggest that GB1, independent of GB2, interacts with Kir3.1 channels [27], induces ERK1/2 phosphorylation and regulates leptin mRNA expression [26], [28]. However, all of these reports failed to detect obvious cell surface expression of GB1 in the absence of GB2.…”
Section: Discussionmentioning
confidence: 99%